Implementation Strategy Instant Assessment To Increase Activity and Result of Learning Mathematics of Al Maksum Junior High School Student (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2017)
Penelitian ini bertujuan untuk mengetahui apakah penerapan strategi pembelajaran Instant Assessment dapat meningkatkan keaktifan belajar matematika siswa dan untuk mengetahui apakah penerapan strategi pembelajaran Instant Assessment dapat meningkatkan hasil belajar matematika siswa. Subjek penelitian ini adalah siswa-siswa kelas VII-3 di SMP Al Maksum Percut Sei Tuan T.P 2014/2015 yang berjumlah 36 orang. Instrumen penelitian yang digunakan adalah tes dan observasi. Hasilnya meningkat pada hasil belajar dan rata-rata keaktifan siswa. Pada siklus I hasil belajar siswa yaitu 44,44% pada siklus ini yang menjadi tujuan dalam penelitian belum tercapai, dan observasi nilai rata-rata keaktifan siswa hanya 2,46. Siklus II Hasil belajar yaitu 75,00% dan nilai rata-rata keaktifan siswa 2,8. Siklus III mencapai ketuntasan hasil belajar siswa 91,67% dan ternyata pada siklus III ini menunjukkan peningkatan dengan rata-rata keaktifan siswa 3,06 dengan kategori baik.This research had purpose for know what the threatment of strategy learning Instant Assessment can increase the student activity for subject math and for knowing what the threatment learning instant assessment can increasing the result in subject math. The subjects of this research was the student of VII-3 in SMP Al Maksum Percut Sei Tuan T.P 2014/2015 the sum of student was 36 people. The instrument of this research used the was test and observation. The resultwas could increase in student outcomes and average of students’ activity. In the circle I the result of student abilitywas 44.44% in this circle become the purpose were not get student achievement and the average of more observation was 2.46. In the circle II the results of student ability was 75.00% and the average mask of observation was 2.8. in the Circle III the result of students ability was 91.67% and as we know the in the circle III to school the increasing of average student achievement of 3.06 it show that student achievement in good category.